Post-traumatic stress disorder symptoms and associated factors in breast cancer patients during the first COVID-19 lockdown in France - Yahi, Feriel; Lequesne, Justine; Rigal, Olivier; Morel, Adeline; Leheurteur, Marianne; Grellard, Jean-Michel; Leconte, Alexandra; Clarisse, Bénédicte; Joly, Florence; Lefèvre-Arbogast, Sophie (Frontiers in Psychology, 2022)
Introduction We aimed to study post-traumatic stress disorder (PTSD) symptoms in breast cancer (BC) patients during the coronavirus disease (COVID-19) pandemic. Materials and methods We included BC patients receiving medical treatment during the first COVID-19 lockdown in France. PTSD symptoms were evaluated using the Impact of Event Scale-Revised (IES-R) questionnaire. Quality of life [Functional Assessment of Cancer Therapy-General (FACT-G)], cognitive complaints [Functional Assessment of Cancer Therapy–Cognitive Function (FACT-Cog)], insomnia [Insomnia Severity Index (ISI)], and psychosocial experiences during lockdown were also evaluated. Multivariable logistic regression was used to identify clinical factors (from medical records) and psychosocial factors (from questionnaires) associated with PTSD symptoms. Results Among the 253 included BC patients (mean age: 58), 46% had metastatic cancer and 52% were treated by chemotherapy alone. COVID-19-induced adjustments in medical oncology practices were experienced by 27% of patients (mainly teleconsultations). No case of COVID-19 was reported; 23% of BC patients had PTSD symptoms. Compared to other patients, patients with PTSD symptoms had more fears relative to COVID-19 infection (83 vs. 60%, p = 0.009), had more feeling of isolation (69 vs. 41%, p = 0.003), and had more prescription or increased use of psychotropic drugs (49 vs. 20%, p = 0.001). In the multivariable model adjusted for clinical factors, fears relative to COVID-19 and increased use of psychotropic drugs were independently associated with PTSD symptoms (OR [95% CI] = 3.01 [1.20–8.44] and 3.45 [1.48–8.17], respectively). Besides, patients with PTSD symptoms had poor quality of life (QoL), and more cognitive complaints and insomnia. Conclusion Post-traumatic stress disorder symptoms were observed in 23% of BC patients during the first COVID-19 lockdown in France. Psychological supports are needed for patients treated during the COVID-19 pandemic.